PENGARUH KINERJA KEUANGAN TERHADAP FINANCIAL DISTRESS DENGAN KEPEMILIKAN MANAJERIAL SEBAGAI VARIABEL MODERASI - Rafqah Annisa Kusumaningrum; Farida Titik Kristanti (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
In facing competition with other business units, a company must maintain its business stability. Individuals who have an interest in an organization trust that this security will keep going quite a while so the organization can keep on running its tasks and can give development to keep up with its business. It is possible for a business to find itself in financial trouble if it is unable to compete with its rivals. This study plans to decide the impact of monetary execution which incorporates the proportion of liquidity, influence, action, and income to monetary misery with administrative proprietorship as a directing variable. Secondary data from the 2017-2021 annual financial reports of companies in the energy sector listed on the Indonesia Stock Exchange were used. MRA and logistic regression are the models that were used in this study. The findings demonstrated that the ratio of liquidity to cash flow can have a significant impact on financial distress, whereas the ratio of leverage to activity cannot have a significant impact on financial distress. Meanwhile, managerial ownership is able to significantly moderate the relationship between the liquidity ratio and financial distress, but not the relationship between the leverage ratio and activity to financial distress. Keywords: Activity; Cash flow; financial distress; leverage, liquidity, managerial ownership